Crisis Communication Strategy as a Solution to Bridge the Peace Agreement Between Kopassus and OPM in West Papua - Youna Chatrine Bachtiar; Linda Purnamasari; Silvia Ratna Juwita (Journal of Social Science, 2022)
The security crisis in West Papua is getting hotter in recent days, although the escalation of the conflict is sometimes high and sometimes low. The shooting of TNI officers assigned there is often the target of gunfire by armed criminal groups in West Papua, as well as innocent local people who are also victims of these incidents. So, it is necessary to hold a mutual peace agreement to reduce losses due to shooting incidents. The crisis communication strategy is considered to be a solution to produce a peace agreement between Kopassus as an institution that represents the Indonesian government and the armed groups or OPM (Free Papua Organization) in West Papua. The crisis communication strategy is considered appropriate to be carried out in the midst of two parties who have different thoughts.